EVALUATION OF ANTIOXIDANT, Α-GLUCOSIDASE AND Α-AMYLASE INHIBITORY ACTIVITIES OF ATALANTIA RACEMOSA AND SENNA UNIFLORA LEAVES - Rahul, Adhav; Subhash, Deokule (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The current investigation was conducted to investigate the total phenol, total flavonoid content, antioxidant, α-glucosidase, and α-amylase activities in leaves of Atalantia racemosa and Senna uniflora. Methods: Different crude solvent extracts were prepared and concentrated using rotary evaporator, these solvent extracts were tested to estimate the antioxidant radical scavenging activity using 1,1-diphenyl-2-picryl-hydrazyl (DPPH) and 2, 2'-azinobis, 3-ethylbenzothiazoline-6-sulfonic acid (ABTS) methods using spectrophotometer. The extracts were screened by α-amylase inhibition assay and α-glucosidase inhibition assay to estimate the antidiabetic potential of the studied plant with the help of microplate reader. Results: A potent antioxidant activity, i.e. mean percentage inhibition of DPPH and ABTS radical was observed in A. racemosa ethanol (71.5 ± 0.026%) and ethyl acetate extract (97.3 ± 0.076%), respectively, at the concentration of 400 μg/mL. Similarly, highest α-amylase and α-glucosidase inhibitory activities were observed in A. racemosa methanolic (82.4 ± 0.016%) and ethyl acetate 91.1±0.018 extracts, respectively. Conclusions: The present study revealed that the A. racemosa extracts possessed good antioxidant, α-amylase and α-glucosidase inhibitory activities; hence, it can be used as a source of natural free radical scavenger and antidiabetic supplement(s). However, further study needs to be carried out to know the active compound and its mode of action.